From Surveillance to Manipulation: How Data Collection Enables Targeted Disinformation - Seabra, Antony; Cavalcante, Claudio; Lifschitz, Sergio (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2025: Anais Estendidos do XL Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd_estendido.2025.248200, 2025)
Surveillance capitalism has fundamentally transformed the digital economy by commodifying personal data to predict and influence behavior. While its economic and ethical implications have been widely studied, less attention has been given to its role in enabling the dissemination of disinformation. This paper explores how the same mechanisms that underpin surveillance capitalism, such as ubiquitous data collection, behavioral profiling, and algorithmic targeting, increasingly mediated by Artificial Intelligence, are leveraged to propagate fake news with unprecedented precision. Drawing from case studies, and empirical research, we demonstrate how actors exploit personalized data to craft and disseminate manipulative content aimed at specific psychological and ideological profiles. By analyzing collected results, we demonstrate that surveillancebased advertising also enables large-scale manipulation, posing serious risks to democratic integrity, public trust, and digital governance.